Efektivitas Layanan Konseling Kelompok untuk Meningkatkan Kedisiplinan Siswa Kelas XI di SMK Negeri 4 Kerinci - Arikal Sandra; Febriady Huta Uruk; Khaidirman Khaidirman (Journal on Education, 2024)
This research is motivated by some students lack of discipline towards school discipline rules, lack of student discipline during the teaching and learning process in class and the ineffective implementation of group counselling services. The purpose of this study is to describe the effectiveness of group counselling services in improving student discipline at SMK Negeri 4 Kerinci. This research uses Pre-Experimental Designs with the One Group Pretest Posttest Design method. The population in this study were all class XI students of SMK Negeri 4 Kerinci, totalling 62 students. The sample in this study used Proposive Sampling technique, with a total of 10 students. Data collection was taken from distributing questionnaires with a Likert Scale. The validity test in this study is using Product Moment Corelation and reliability test using Alpha Cronbach. Data analysis techniques in this study using Paired t-test and Wilcoxon t-test. Based on the results of the research that has been done, the paired t test results show that the significant value is 0.00, which means 0.00 <0.05, so Ho is rejected and Ha is accepted. And the results of the calculation of the wilcoxon signed rank test, known Asymp. Sig (2 tailed) 0.03 because the value of 0.005 is smaller than 0.05, it can be concluded that Ha is accepted while Ho is rejected. This means that there is a significant increase between group counselling in improving student discipline in class XI students at SMK Negeri 4 Kerinci.